Characterization of Extracellular Signal-Regulated Kinase 5 Levels in Human Umbilical Vein Endothelial Cells Exposed to Disturbed and Uniform Flow - Shalaby, Sherif; Chitragari, Gautham; Sumpio, Brandon J.; Sumpio, Bauer E. (International Journal of Angiology, 2014)
Extracellular signal-regulated kinase 5 (ERK5) has been reported to regulate endothelial cell integrity and protect from vascular dysfunction under continuous laminar flow. However, the effect of flow on ERK5 levels has not been determined. Confluent human umbilical vein endothelial cells (HUVECs) were seeded on fibronectin coated glass slides and serum starved for 2 hours with 1% fetal bovine serum (FBS). HUVECs were then exposed to to and fro flow (TFF), pulsatile forward flow (PFF), or continuous laminar flow (CLF) in a parallel plate flow chamber for up to 2 hours. At the end of experiment, cell lysates were prepared and immunoblotted with antibodies to total ERK5. Both CLF and TFF exhibited a decrease in ERK5 after levels after 2-hour exposure. However, the level of ERK5 for PFF remained the same. Disturbed, but not uniform pulsatile, flow decreases ERK5 levels in HUVECs.
Keywords: pulsatile uniform flow; atherosclerosis; HUVECs; ERK5; disturbed flow; laminar flow; uniform flow